Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/bmt.2011.78
|View full text |Cite
|
Sign up to set email alerts
|

Fertility after allogeneic haematopoietic stem cell transplantation in childhood and adolescence

Abstract: Infertility is a major late effect in patients receiving haematopoietic stem cell transplantation (HSCT). The aim of this study was to determine the proportion of patients having fertility impairment after allogeneic HSCT in childhood/adolescence and to identify the potential risk factors. Treatment and fertility data of paediatric patients with malignant and non-malignant diseases treated with allogeneic HSCT between 2000 and 2005 were collected from seven European centres. Data were obtained for 138 female a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(138 citation statements)
references
References 19 publications
5
123
1
4
Order By: Relevance
“…57 Literature indicates that such discussions occur ~10% of the time at the start of gonadotoxic therapy for adults. 62 Among children diagnosed with cancer, these discussions occur even more rarely, as it is a great challenge for physicians to bring up fertility amidst a conversation of life-threatening diagnoses and therapies.…”
Section: Infertility Resourcesmentioning
confidence: 99%
“…57 Literature indicates that such discussions occur ~10% of the time at the start of gonadotoxic therapy for adults. 62 Among children diagnosed with cancer, these discussions occur even more rarely, as it is a great challenge for physicians to bring up fertility amidst a conversation of life-threatening diagnoses and therapies.…”
Section: Infertility Resourcesmentioning
confidence: 99%
“…Younger age is associated with an increased likelihood of fertility recovery. 2 Previous studies indicated that fertility is most frequently preserved in patients receiving a transplant in the young adult age group (15-30 years). 8 This was supported by our study, which showed that age > 30 years at Allo-HSCT was related to increased risk of infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Borgmann-Staudt et al reported that impaired fertility was observed 3-12 years after the treatment in 69% of male patients and 83% of female patients who received allo-HSCT at an early age. 2 High doses of alkylating agents and/or total body irradiation (TBI) as well as older age in women at the time of transplant were found to be related to gonadal dysfunction and infertility. 3 Recovery of fertility after HSCT therapy has been reported in both sexes; in males the rate of spermatogenesis may increase with time.…”
Section: Introductionmentioning
confidence: 99%
“…2 While few cases of successful conception or spermatogenic recovery after HSCT, with chemotherapy alone, or combined with TBI conditioning, have been reported 1, [3][4][5][6][7][8][9][10][11][12] (Table 1), other studies assessing male fertility after HSCT have not reported any conception, highlighting the increased risk of altered reproductive function after HSCT. In 2010, the patient was still in complete remission.…”
Section: Dear Editormentioning
confidence: 99%